Microstructures Behavior in Biomedical Co-Cr-Mo-C-Si-Mn Alloys Containing Nitrogen - Alfirano Alfirano (Institut Teknologi Sepuluh Nopember, 2014)
The precipitates in as-cast and heat-treated biomedical Co-28Cr-6Mo-0.25C-0.175N-(0–1)Si-(0–1)Mn alloys (wt.%) were investigated. The precipitates observed in the as-cast and heat-treated Co-Cr-Mo-C-N alloys were of the M23X6 type, M2X type, p-phase, and h-phase. A blocky-dense p-phase precipitate and a lamellar cellular colony, which consisted of an M2X type precipitate and a g-phase, were mainly detected in the as-cast alloys with and without added Si, respectively. The addition of nitrogen caused cellular precipitation, while the addition of Si suppressed it and enhanced the formation of the π-phase. The addition of nitrogen decreased the time required for complete precipitate dissolution at low heat-treatment temperatures. At high temperatures, complete precipitate dissolution was delayed by the partial melting that accompanied the formation of the precipitates such as the p-phase